2001
DOI: 10.1007/s007020170098
|View full text |Cite
|
Sign up to set email alerts
|

A study of excessive daytime sleepiness and its clinical significance in three groups of Parkinson's disease patients taking pramipexole, cabergoline and levodopa mono and combination therapy

Abstract: a) EDS is not unique to pramipexole therapy and occurs with both cabergoline and levodopa. b) Increasing age, advanced disease, and higher treatment dose appear important predictors for EDS. c) Driving regulations should be reviewed accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
32
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 8 publications
7
32
5
Order By: Relevance
“…This assumption is further supported by a recently published trial reporting no significant difference in the occurrence of daytime sleepiness under a therapy with PPX, cabergoline, or levodopa. 24 Thus, unusually fast or sudden onset of sleep in our patients was possibly rather caused by the overall increase in dopaminergic medication than specifically by the administration of PPX or ROP. This might particularly be the case in Patients 5 and 6 who also received a high dose of the ergot DA cabergoline.…”
Section: Discussionmentioning
confidence: 96%
“…This assumption is further supported by a recently published trial reporting no significant difference in the occurrence of daytime sleepiness under a therapy with PPX, cabergoline, or levodopa. 24 Thus, unusually fast or sudden onset of sleep in our patients was possibly rather caused by the overall increase in dopaminergic medication than specifically by the administration of PPX or ROP. This might particularly be the case in Patients 5 and 6 who also received a high dose of the ergot DA cabergoline.…”
Section: Discussionmentioning
confidence: 96%
“…Others have similarly shown that dopamine agonists [45] and the total levodopa equivalent dose [3,14] are associated with EDS. Additionally, patients on levodopa monotherapy had lower risk for sleep attacks than patients on dopamine agonist monotherapy or patients on a combination of levodopa and a dopamine agonist [16].…”
Section: Discussionmentioning
confidence: 99%
“…Longer disease duration [1,40] and association with UPDRS III [41] and the HY stage [14,18,41] have been reported. In our series, patients with advanced/severe PD (HY ≥3) did not differ from patients with light/beginning PD (HY <3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr. Chaudhuri presented data from his group suggesting that cabergoline, given in the evening, was superior to levodopa and other short-acting agonists in relation to tolerance, compliance, and alleviation of nighttime motor symptoms in PD. Issues in relation to sleepiness associated with dopamine agonist therapy [7] and treatment of advanced dyskinetic PD patients using daytime apomorphine and evening dosing of cabergoline were also discussed. …”
mentioning
confidence: 99%